Ovarian hormones, but not fluoxetine, impart resilience within a chronic unpredictable stress model in middle-aged female rats. (August 2016) - Mahmoud, Rand; Wainwright, Steven R.; Chaiton, Jessica A.; Lieblich, Stephanie E.; Galea, Liisa A.M.
Abstract: Depression is more prevalent in women than in men, and women are at a heightened risk for depression during the postpartum and perimenopause. There is also evidence to suggest that the ovarian hormone milieu may dictate antidepressant efficacy. Thus, it is important to investigate the role of ovarian hormones in the pathogenesis of depression and in the mechanisms that may underlie antidepressant efficacy. In the present study, we used 10-month-old female Sprague-Dawley rats to examine the effects of long-term ovarian hormone deprivation on the development of depressive-like endophenotypes after chronic stress, and on antidepressant efficacy. Four months following ovariectomy (OVX) or sham surgery, all rats were subjected to 6 weeks of chronic unpredictable stress (CUS). During the last 3 weeks of CUS, rats received daily injections of fluoxetine (5 mg/kg) or vehicle. All rats were assessed on measures of anxiety- and depressive-like behavior, hypothalamic-pituitary-adrenal (HPA) negative feedback inhibition, and on markers of neurogenesis and microglia in the dentate gyrus. Our findings demonstrate that long-term ovarian hormone deprivation increased anxiety and depressive-like behavior, as seen by increased immobility in the forced swim test and latency to feed in the novelty suppressed feeding test, and decreased sucrose preference. Further, long-term OVX resulted in impaired HPA negative feedback inhibition, as seen in the dexamethasone suppression test. Fluoxetine treatment showed limited behavioral and neuroendocrine efficacy, however it reduced microglial (Iba-1) expression, and increased cell proliferation, neurogenesis (via cell survival), and the expression of the polysialylated neuronal cell adhesion molecule (PSA-NCAM) in the dentate gyrus, although these effects varied by region (dorsal, ventral) and ovarian status. Taken together, our findings demonstrate that ovarian hormones may impart resilience against the behavioral and neuroendocrine consequences of chronic unpredictable stress, and may modulate the effects of fluoxetine on cell proliferation, neurogenesis, and PSA-NCAM in the middle-aged female. Highlights: Long-term ovariectomy (OVX) increased depressive like-behavior in chronically stressed rats. Long-term OVX altered basal and stress corticosterone levels in chronically stressed rats. Fluoxetine increased neurogenesis and PSA-NCAM in the hippocampus in an ovarian status dependent manner. Fluoxetine reduced microglial number in the ventral hippocampus of chronically stressed rats.